Brandon Hopper: capstone - Hopper, Brandon, artist (Colorado State University. Libraries, 2017)
The artist's statement: I like to consider myself an interdisciplinary artist. The points where different mediums and art forms overlap are where I like to operate. I believe that all art and design is a combination of different ideas and influences. I love the idea of collaboration. People all have a unique point of view and a unique methodology. When you combine your ideas with another, you can create some truly incredible things. Video is a great medium for collaboration. You can capture someone's talents, passions, and experiences to tell a unique story about it. Not only is the idea of collaboration beautiful in itself, but it also creates the best work. Even on a solo project, feedback is vital. Transformation is also a key element in my work. I like to take an object or space and transform it's use or perception. When you see something used in a way that is unusual, even if it is a practical use, it broadens your idea of what art can be.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design